Kepuasan Kerja Ditinjau dari Adversity Quotient dan Work Family Conflict pada Perawat Wanita yang Telah Menikah di Rumah Sakit Umum Daerah Dr. RM. Djoelham Binjai - Rina Mirza; Diny Atrizka (Faculty of Psychology, Universitas Medan Area, 2018)
This research aims to determine the relationship between adversity quotient and work family conflict with job satisfaction. The hypothesis states that there is a relationship between adversity quotient and work family conflict with job satisfaction. This research uses quantitave method, especially the correlational technique. The subjects were 76 married female nurses at RSUD Dr. RM Djoelham Binjai. Total sampling technique was used in this study. The datum collected through Scale of Job Satisfaction, Adversity Response Profile (ARP) and Work Family Conflict Scale. The collected data then analyzed with multiple regression analysis method. The main result of this study showed that there was a significant correlation between adversity quotient and work family conflict with job satisfaction (R = 0,462; p < 0,05). Based on the result, there is a relationship between adversity quotient and work family conflict with job satisfaction. It can be concluded that the hypothesis is accepted.